Adaptasi Guru Pendidikan Agama Islam dalam Digitalisasi Pembelajaran Pasca Pembelajaran Jarak Jauh (Studi Kasus di SMP Negeri 2 Bojong, Kab. Tegal, Jawa Tengah) - Tomi Azami; Basukiyatno Basukiyatno (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to analyze and describe the pattern of adaptation of Islamic Religious Education Teachers (PAI) on the phenomenon of digitalization of learning. The phenomenon of using digital in learning begins with the phenomenon of Distance Learning (PJJ) as a response to the emergence and outbreak of Covid-19 which has become a pandemic in Indonesia. This research uses a qualitative approach with a case study approach. The research locus is at SMP Negeri 2 Bojong. Geographically, SMP Negeri 2 Bojong is located in a mountainous area. The reason for choosing the locus is the peculiarity of the locus because it is located in a mountainous area while digitization is closely related to urban areas. The informant selection technique is purposive sampling, which is selecting informants based on the criteria determined by the researcher. Data collection is done by means of observation, interviews and documentation, the data will be analyzed using Miles and Huberman's interactive analysis technique. The results showed that PAI teachers at SMP Negeri 2 Bojong were fully prepared. The teacher uses the "Student PAI" application in carrying out the PJJ process. While the application used by the teacher in providing material, evaluation, and follow-up uses the "AGPAII MODUL" application. Both applications can be downloaded on the Playstore, even one of the PAI teachers at the school is part of the development team. The geographical location at the foot of Slamet Mountain is not an obstacle for teachers to adapt to distance learning’s policies.Keywords: Adaptation, PAI Teacher, Digitalization of Learning, Distance Learning